Diagnostic Accuracy of Fine Needle Aspiration Cytology and Shear Wave Elastography in Diagnosis of Malignant Thyroid Nodules Taking Post-Operative Histopathology as Gold Standard - Zafar, Sadia; Khalid, Abubakar; Bakht, Khush; Mazhar, Saadoon (Indus Journal of Bioscience Research, 2025)
Background: Precise diagnosis of malignant thyroid nodule is a very important aspect in directing the clinical approach, and in preventing unnecessary surgeries. This had been the standard diagnostic modality for a long time; Fine needle aspiration cytology (FNAC). yet, its loopholes in indeterminate cytological categories have generated an interest in non-invasive such as shear wave elastography (SWE) which measures tissue stiffness. Aim: To compare the diagnostic accuracy of FNAC and SWE for diagnosis of the malignant thyroid nodules, compared to a histopathology reference standard. Methods: This cross-sectional study was undertaken at the Department of Radiology, Lahore General Hospital in six months. 170 patients aged 20–60 years with ultrasound suspicious thyroid nodules were examined. Each patient received SWE performed by an experienced radiologist, FNAC and later histopathological confirmation. Diagnostic performance was estimated within the boundaries of sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy. Analysis of Data was performed in SPSS version 22.0. Results: SWE showed superior diagnostic performance with a specificity of 98.6%, sensitivity of 69.2%, PPV of 90.0%, NPV of 94.8%, and an overall diagnostic accuracy of 94.1%. SWE score 4 was highly predictive of malignancy, while score 1 reliably excluded it. In contrast, FNAC achieved 80% sensitivity and 85% specificity when Bethesda categories B3–B6 were considered malignant. Diagnostic performance of FNAC improved to 100% sensitivity and 90% specificity when only B5–B6 were classified as malignant. Histopathology confirmed that solitary nodules were more often malignant than multiple nodules. Conclusion: SWE demonstrated better overall diagnostic accuracy and non-invasiveness compared to FNAC, particularly in stratifying benign versus malignant nodules. While FNAC remains essential for cytological confirmation, SWE offers substantial advantages in specificity and can effectively guide biopsy decisions, especially in clearly benign or highly suspicious cases.